TINDAK PIDANA NARKOTIKA: ANTARA REHABILITASI DAN PEMIDANAAN DALAM PERSPEKTIF SISTEM PERADILAN PIDANA - Novi Maimory, Aminoel Akbar; Sutrisno, Hafiz (Pahlawan Tuanku Tambusai University, 2025)
Drug abuse in Indonesia has reached alarming levels and is impacting national resilience. Law enforcement faces the dilemma of whether to position addicts as perpetrators or victims requiring rehabilitation. Although Law Number 35 of 2009 concerning Narcotics regulates rehabilitation policies, criminal justice practices still emphasize punishment. This research uses a normative juridical method with a statutory, conceptual, and case study approach. The results indicate that the orientation of criminal justice remains predominantly focused on punishment, while rehabilitation is suboptimal due to limited regulations, facilities, and the paradigm of law enforcement officers. This article recommends more proportional criminal policy reforms by emphasizing rehabilitation for addicts and strict punishment for dealers and dealers. Keywords : Narcotics Crimes, Punishment, Rehabilitation, Criminal Justice System.